Exploring the Benefits of Affectionate Communication: Implications for Interpersonal Acceptance–Rejection Theory. Issue 4 (13th December 2017) - Denes, Amanda; Bennett, Margaret; Winkler, Kara L.
Abstract: In the past several decades, a robust line of research has developed in the field of communication exploring the interpersonal outcomes of receiving and giving affection. The present review offers an in‐depth examination of research on affectionate communication and its implications for understanding interpersonal acceptance and rejection. The review begins by introducing the primary theoretical framework used to explore affectionate communication, followed by an overview of the benefits of receiving and giving affection. Following this review, the implications of affectionate communication for acceptance–rejection researchers are presented, including a discussion of the complexities of affection and what such intricacies may mean for future theorizing in this domain. Lastly, future directions for acceptance–rejection research in light of this review are presented.